The Use of Arabic Sound in Teaching English Pronunciation Through Flashcard: Research and Development - Nurabianti, Asfian; Farah, Rafika Rabba (Journal of Languages and Language Teaching, 2024)
Pronunciation is one of important aspects in learning a foreign language especially English. Good pronunciation can be easily processed by listeners, but inaccurated pronunciation can cause misunderstanding in communication. However, there are some difficulties found in EFL students in learning English pronunciation. Therefore, this research aims to develop Hijaiyah Flashcard as a medium in teaching English pronunciation which introduces several English consonants that have similar sound to the hijaiyah letters or Arabic consonants, while Indonesian students are familiar with the sound of hijaiyah letters. In developing the media, this research used Research and Development (R&D) as a research method. The subjects of the research were media expert, English teacher and second grade students of SMP Muhammadiyah Malang. The data were gained by doing the observation, interview and distributing questionnaires. Flashcards are developed and revised based on the assessment given. The validation scores obtained from media expert’s questionnaire is 82.5% and from English teacher is 100%. It means that the medium is feasible to use in teaching English pronunciation. In addition, the total score from students’ queastionnaire is 84,25 %. Thus, by introducing the similarity of sounds between English and Arabic consonants through Hijaiyah Flashcard, it can be a medium that teacher can use in teaching English pronunciation.